Nutritional aspects in the chronic critical patient, a Systematic Review - Cavalcanti de Freitas Ferreira, Ana Carolina; Lipovesky, Fernando (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
The term "chronically critically ill" is used to describe a group of patients who remain dependent on life-sustaining therapies after a severe acute illness requiring intensive care unit (ICU) admission. Malnutrition is a common finding among chronically critical patients and has been associated with negative effects. Nutritional support has gained recognition as a beneficial therapeutic strategy, not only to prevent loss of body mass, but also to attenuate metabolic alterations induced by prolonged stay in the ICU. Therefore, the objective of this study was to determine the relationship between malnutrition and poor outcomes in chronically critical patients. For this study, a systematic review was carried out in the PubMed, Scielo, Google Scholar, Clinical Trials and Bookshelf databases. Articles published in the period from 2017 to 2022, in English, were selected. A total of 2,836 articles were found. Subsequently, it was selected from the reading of titles and abstracts, resulting in the exclusion of 2,543 articles. Afterwards, 246 were read in their entirety and the inclusion and exclusion criteria were applied. And so, only 10 were eligible for analysis in the present study. The current literature unifies supportive care for ECC patients through two crucial strategies: early mobilization, and anabolic nutrition. In addition, it shows the role of protein and anabolic supplements, immunonutrition and among others. In ECC, the malnourished patient can increase the length of stay in the ICU, the incidence of infections and hospital mortality. Thus, as the authors state, to solve these problems there is nutritional support, which can mitigate the negative effects of macronutrient or micronutrient deficiencies, as well as several other nutritional interventions that have already been studied